Implementation of Murabahah Contract on Employee Welfare Financing Products at Bank BJB Syariah KCP Indramayu - Aden Bagas Gumelar (Konsultan Jurnal Ilmiah Indonesia, 2025)
Research conducted at Bank BJB Syariah KCP Indramayu regarding the application of the murabahah contract to Employee Welfare Financing (PKP) products shows that the murabahah contract is applied in the form of buying and selling, where goods are sold at a mutually agreed price along with a profit margin. The PKP financing process includes several stages, such as applying for financing, verifying customer data, assessing customer eligibility, financing approval, signing the contract, and disbursing funds. This entire process is in accordance with the pillars and conditions of the murabahah contract which refer to the National Sharia Council Fatwa No. 04/DSNMUI/IV/2000 concerning murabahah. The financing provided in this PKP product is sharia financing, the implementation of which is in accordance with Islamic law. In sharia financing products, giving interest or usury is prohibited, and instead, financing is carried out based on the principle of profit sharing according to the agreement between the bank and the customer. Thus, the implementation of the murabahah contract on PKP products at Bank BJB Syariah KCP Indramayu has been carried out in accordance with sharia provisions, providing financing solutions to employees in a fair manner and in accordance with Islamic law.